Perisomatic Voltage-Gated Sodium Channels Actively Maintain Linear Synaptic Integration in Principal Neurons of the Medial Superior Olive - Scott, Luisa L. (Society for Neuroscience, 2010)
Principal neurons of the medial superior olive (MSO) compute azimuthal sound location by integrating phase-locked inputs from each ear. While previous experimental and modeling studies have proposed that voltage-gated sodium channels (VGSCs) play an important role in synaptic integration in the MSO, these studies appear at odds with the unusually weak active backpropagation of action potentials into the soma and dendrites. To understand the spatial localization and biophysical properties of VGSCs, we isolated sodium currents in MSO principal neurons in gerbil brainstem slices. Nucleated and cell-attached patches revealed that VGSC density at the soma is comparable to that of many other neuron types, but channel expression is largely absent from the dendrites. Further, while somatic VGSCs activated with conventional voltage dependence (V(1/2) = −30 mV), they exhibited an unusually negative range of steady-state inactivation (V(1/2) = −77 mV), leaving ∼92% of VGSCs inactivated at the resting potential (approximately −58 mV). In current-clamp experiments, non-inactivated VGSCs were sufficient to amplify subthreshold EPSPs near action potential threshold, counterbalancing the suppression of EPSP peaks by low voltage-activated potassium channels. EPSP amplification was restricted to the perisomatic region of the neuron, and relatively insensitive to preceding inhibition. Finally, computational modeling showed that the exclusion of VGSCs from the dendrites equalizes somatic EPSP amplification across synaptic locations and lowered the threshold for bilateral versus unilateral excitatory synaptic inputs. Together, these findings suggest that the pattern of sodium channel expression in MSO neurons contributes to these neurons' selectivity for coincident binaural inputs.